The effect of prolonged intense physical exercise of special forces volunteers on their plasma protein denaturation profile examined by differential scanning calorimetry. (February 2021) - Mourtakos, Stamatis; Philippou, Anastassios; Papageorgiou, Anastasios; Lembessis, Peter; Zaharinova, Stella; Hasanova, Yozlyam; Koynova, Rumiana; Bersimis, Fragiskos; Tenchov, Boris; Geladas, Nikolaos; Mikros, Emmanuel; Sidossis, Lampros S.; et al.
Abstract: The human blood plasma proteome profile has been an area of intensive investigation and differential scanning calorimetry (DSC) has come forward as a novel tool in analyzing plasma heat capacity changes to monitor various physiological responses in health and disease. This study used DSC to assess potential alterations in the plasma heat capacity profile of albumin and globulins during extremely demanding physical exercise. We monitored the changes in denaturation profiles of those plasma proteins for five consecutive days of an extraordinary exercise training schedule in 14 young male Special Forces volunteers, as well as after a 30-day recovery period. The major effect of the prolonged intense exercise was the continuous upward shift of the albumin peak by 2°–3 °C on the initial days of exercise, with a tendency to plateau circa the 5th day of exercise. In addition, some redistribution of the denaturational enthalpy was observed upon exercise, where the globulins peak increased relative to the albumin peak. Noteworthy, the alterations in the plasma proteome denaturational profiles were not persistent, as virtually full recovery of the initial status was observed after 30 days of recovery. Our findings indicate that 5 days of exhaustive physical exercise of highly trained individuals enhanced the thermal stability of plasma albumin shifting its denaturational transition to higher temperatures. We surmise that these effects may be a result of increased blood oxygenation during the prolonged intense exercise and, consequently, of albumin oxidation as part of the overall adaptation mechanisms of the body to extreme physical and/or oxidative stress. Highlights: Differential Scanning Calorimetry (DSC) and plasma heat capacity profile of proteins in response to intense exercise. Denaturational transition of plasma albumin thermal stability after prolonged rigorous physical stress in trained subjects. Increased oxidative stress induces ROS production which alters the structural conformation of plasma albumin. The plasma albumin redox state may reveal the optimum oxidative stress for exercise-induced adaptations of skeletal muscle.